P5.055 Building a National Coalition For Sexual Health in the US: Overview of a Participatory Approach with Key Stakeholders. (13th July 2013) - Loosier, P S; Coffield, A; Ward, A; Gilbert, S
Abstract : In 2011, Partnership for Prevention (Partnership) collaborated with the US Centers for Disease Control and Prevention to develop a domestic National Coalition for Sexual Health (NCSH). The NCSH's stated mission was to normalise sexual health among the general population and to promote sexual health among populations at higher risk. To develop the Coalition's vision, mission, goals, and priorities, Partnership conducted a series of systematic in-depth interviews with key stakeholders and held consultations with experts in the fields of healthcare, communications, sexual violence prevention, public policy, and sexual health education. Key findings included: (1) The need to give meaning to and build acceptance of the concept of "sexual health" to mainstream sexual health among influential sectors (e.g., media) and the general public; (2) Providing national leadership around sexual health will have downstream benefits for a range of stakeholders, including those focusing on a single aspect of sexual health or specific target audiences; (3) There is possible risk to leaving the traditional disease reduction/disaster avoidance framework and initial work should work to obviate this risk; and, (4) There is broad support for the benefits of a sexual health approach (e.g., coordinating and leveraging resources across national partners). Findings: from these interviews and consultations were used to shape the NCSH's foundation and framing, and feedback was again sought from these key stakeholders, along with others, to gain consensus and build support for the new Coalition. This iterative process resulted in a Coalition mission, goals, values, expected member roles, and priority areas of focus which represented the breadth of key stakeholder concerns and priorities. These foundational principles will be presented in depth. Within fourteen months of project start-up, 25 organisations have joined the NCSH and are actively participating in its Action Groups. This participatory, consensus-building approach could hold promise for other coalition-building efforts.